Casting a giant shadow : the transnational shaping of Israeli cinema - Harris, Rachel S. (Rachel Sylvia), 1977-; Chyutin, Dan (New directions in national cinemas., 2021)
"Film came to the territory that eventually became Israel not long after the medium was born. Casting a Giant Shadow is a collection of articles that embraces the notion of transnationalism to consider the limits of what is "Israeli" within Israeli cinema. As the State of Israel developed, so did its film industries. Moving beyond the early films of the Yishuv, which focused on the creation of national identity, the industry and its transnational ties became more important as filmmakers and film stars migrated out and foreign films, filmmakers, and actors came to Israel to take advantage of high-quality production values and talent. This volume, edited by Rachel Harris and Dan Chyutin, uses the idea of transnationalism to challenge the concept of a singular definition of Israeli cinema. Casting a Giant Shadow offers a new understanding of how cinema has operated artistically and structurally in terms of funding, distribution, and reception. The result is a thorough investigation of the complex structure of the transnational and its impact on national specificity when considered on the global stage"--